Atividade antileucêmica de derivados de imidazo[1,2-a]piridina in vitro - GABRIELLA TELES BURKNER (2022)
The chronic myeloid leukemia (CML) is a myeloproliferative disorder and accounts for 15% of adult leukemia. Compounds containing imidazo[1,2-a]pyridine have been used in medicinal chemistry and drug development because are correlated with many therapeutic properties including an important strategy in drug research of chemotherapeutic agents. These compounds promote oxidative stress in cells thereby inducing senescence or apoptosis. The present scientific research used compounds containig imidazo[1,2-a]pyridines in leukemic cell lines and investigated the antitumor effects. The imidazo[1,2-a]pyridines were synthesized and the oral biovailability and toxicity were analysed using SwissADME software and Osiris® Property Explorer respectively. Human leukemic cell lines Kasumi, KG-1, K562 and Jurkat were grown and cultivated in appropriate conditions. The screening was performed based on redox effect and the best oxidative profile was selected for the following stages of study. The citotoxicity assay was analyzed using fluorescence flow cytometry and MTT. Cell proliferation was assessed by cell counting was performed using a Neubauer chamber. After the induction of senscence was evaluated through the expression of SA- β-galactosidase by cytochemistry. Oxidative stress was evaluated by determination of lipid peroxidation using the TBARS assay (substances that react with thiobarbituric acid) and by the reduced glutathione (GSH) content. The predictive analysis showed a possible effect on the reproductive system. However, it does not suggest mutagenic, carcinogenic or irritability effects. MRK-107 against K562 cells was the imidazo[1,2-a]pyridines derivative that showed the best redox profile for the experiments. However, MRK-107 was not able to induce death in K562 and monocyte cells. On the other hand, this compound was able to inhibit cell proliferation and induced cell senescence after 72 hours. Furthermore, the MRK-107 compound induced oxidative stress in K562 cells after 72h of exposure, increasing lipid peroxidation and decreasing the GSH content. Thus, this study demonstrated that the senescence induced by the compound MRK-107 has the involvement of oxidative stress as a possible mechanism of action, being a potential antitumor mechanism in the chemotherapy of cancer cells using compounds derived from imidazo[1,2-a]pyridine against the CML.